2021
DOI: 10.4236/jss.2021.910010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Total Foreign Debt on the Economic Growth of Egypt (1980-2018)

Abstract: Foreign debt is considered to be a source of income for countries. If foreign debt is managed well and directed towards productive projects, then it might enhance the countries' economic growth. However, foreign debt has many costs that might cause deterioration in the economy. This study aims to investigate how total foreign debt impacts the economic growth of Egypt for a time period of 39 years . In the methodology, descriptive statistics, unit root tests, Johansen co-integration and Vector Error Correction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…This result is also supported by several previous studies conducted by Kharusi & Ada (2018) in Oman, Awan & Qasim (2020) in Pakistan, Safwat, Salah & Sherif (2021) in Egypt, and Sari (2022) in Indonesia which found that foreign debt harms economic growth. Furthermore, Safwat, Salah & Sherif (2021) stated that the negative relationship between external debt and economic growth is because a large amount of money must be given as debt repayment and the amount of debt slows down the process of economic growth and increases the country's dependence on foreign resources.…”
Section: Relationship Between Foreign Debt and Economic Growthsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is also supported by several previous studies conducted by Kharusi & Ada (2018) in Oman, Awan & Qasim (2020) in Pakistan, Safwat, Salah & Sherif (2021) in Egypt, and Sari (2022) in Indonesia which found that foreign debt harms economic growth. Furthermore, Safwat, Salah & Sherif (2021) stated that the negative relationship between external debt and economic growth is because a large amount of money must be given as debt repayment and the amount of debt slows down the process of economic growth and increases the country's dependence on foreign resources.…”
Section: Relationship Between Foreign Debt and Economic Growthsupporting
confidence: 86%
“…However, Kikuchi & TBe (2021), Suidarma &Yasa (2021), andDarmawati, Suparta &Saimul (2021) argue that there is a positive influence of external public debt on Indonesia's economic growth. Meanwhile, Safwat, Salah & Sherif (2021), Kurniasih (2021), Awan & Qasim (2020), Annisa, Nairobi & Taher (2022), and Sari (2022 stated that there is a negative relationship between external public debt and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that greater openness to international trade leads to an increase in the growth rate. The positive impact of an increase of trade openness on economic growth has been demonstrated in many empirical studies (Safwat, Salah, El Sherif, 2021). (Joshua, Adedoyin, Sarkodie, 2020 ) reached the same conclusion for South Africa confirming the trade-induced growth hypothesis.…”
Section: Results Of the Researchmentioning
confidence: 52%
“…They revealed a long-run equilibrium relationship between FDI and other control variables and established that, in the short run, the effect of GDP and GNI volatility on FDI is negligible. Conversely, Safwat et al [24] utilized Johansen cointegration and vector error correction methods with observations from 1980 to 2018 to examine the effect of FDI on economic growth. Their results indicate a long-term linkage between FDI inflows and growth, concluding that FDI has a positive impact.…”
Section: Empirical Reviewmentioning
confidence: 99%